2020
DOI: 10.1021/acsami.0c17429
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Sintering-Based 4D Printing of Magnetism-Responsive Grippers

Abstract: Components fabricated by four-dimensional (4D) printing hold the potential for applications in soft robotics because of their characteristics of responding to external stimuli. Grippers, being the common structures used in robotics, were fabricated by the selective laser sintering (SLS)-based 4D printing of magnetism-responsive materials and tested for remote-controllable deformation in an external magnetic field. A composite material consisting of magnetic Nd2Fe14B powder and thermoplastic polyurethane powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…AM is transforming the manufacturing industry with the ability to produce geometrically simple to highly complex and delicate structures. With a variety of 3D printing processes available for a wide range of materials, 3D printing has been extensively adopted in a number of different fields including but are not limited to mechanical engineering, civil [253], (b) 4D effect of a gripper under an external magnetic field, produced via SLS printing [266], and (c) 4D effect of flower-like structure and folding of 2D to the 3D structure under an external magnetic field, produced via DLP printing [255].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…AM is transforming the manufacturing industry with the ability to produce geometrically simple to highly complex and delicate structures. With a variety of 3D printing processes available for a wide range of materials, 3D printing has been extensively adopted in a number of different fields including but are not limited to mechanical engineering, civil [253], (b) 4D effect of a gripper under an external magnetic field, produced via SLS printing [266], and (c) 4D effect of flower-like structure and folding of 2D to the 3D structure under an external magnetic field, produced via DLP printing [255].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the thermal behaviour of the surface functionalized PA12 is similar to that of virgin PA12 powders ( Figure 10 e). In another very recent study (2021), micron-sized fillers (Nd-Fe-B) are used together with TPU [ 266 ]. Therein, composite is prepared just by blending the polymer and fillers, silica nanoparticles are added to improve the flowability.…”
Section: Towards Magneto-active 4d Printingmentioning
confidence: 99%
See 3 more Smart Citations